Chalcone-containing phthalocyanines: Determination of photophysical and photochemical properties and cytotoxicity on breast cancer cell models - Kucuk, Tugba; Harmandar, Kevser; Aydogdu, Bahar; Goksel, Meltem; Balcik-Ercin, Pelin; Ibisoglu, Hanife; Atilla, Devrim (World Scientific Publ Co Pte Ltd, 2025)
The synthesis of new Zn(II), and Si(IV) phthalocyanine (Pc) derivatives containing chalcone group was successfully achieved and the compounds were characterized by MALDI-TOF mass spectroscopy, FT-IR, H-1 NMR, C-13 NMR, and UV-vis spectral data. The photophysical and photochemical properties of these novel Pcs were investigated in DMF. The in vitro cytotoxic effect of the compounds on mammary breast adenocarcinoma cell lines (MCF-7 and MDA-MB-231) and normal mammary breast epithelium (MCF-12A) were evaluated by using the WST assay. Based on the WST assay analysis, cytotoxicity of the Pc derivatives to mammary breast carcinoma cells was compared to normal mammary breast epithelium cells dependent on light illumination. The results of the present investigation demonstrate that all the Pc derivatives containing the chalcone group have a phototoxic effect on mammary breast cancer cells and could be promising photodynamic therapy (PDT) agents for further studies.
Keywords: phthalocyanine; chalcone; photochemical; photophysical; PDT; cytotoxicity